Relationship between organizational culture and job satisfaction based on Denison model / Sayyed Mohsen Allameh and Ahmad Reza Akhavan Sarraf - Allameh, Sayyed Mohsen; Akhavan Sarraf, Ahmad Reza (Faculty of Business Management, 2013)
Previous research shows a significant relationship between organizational culture and job satisfaction. Given the increasing importance of job satisfaction in organizations, this study examines the relationship between organizational culture and job satisfaction in an industrial health unit. Dennison’s Organizational Culture Questionnaire been used to measuring organizational culture and Job Descriptive index from Smith and Kendall been used to review employee’s job satisfaction and simple random method also used for sampling. Research findings show that organizational culture is in the average level and job satisfaction is in fairly high level. Also, using the Pearson correlation between organizational culture and job satisfaction shows a positive relation between variables. Linear regression was also used to determine the organization's corporate culture can predict job satisfaction